Determinants of HIV/AIDS Prevention Behavior Among Men Who Have Sex with Men: A Mixed-Methods Study in Palu, Indonesia - Fadjriah, Rasyika Nurul; Khairunnisaa; Mu’minsyah; Arifuddin, Adhar; Rahman, Abd (YCAB Publisher, 2025)
Background: Human Immunodeficiency Virus (HIV) and Acquired Immune Deficiency Syndrome (AIDS) remain global health challenges, particularly among men who have sex with men (MSM), who face biological and social vulnerabilities. In Indonesia, MSM represent a key population with high HIV prevalence, and Palu City reports the highest number of HIV cases in Central Sulawesi, underscoring the need for targeted prevention. Objectives: This study examined the relationship between knowledge, attitudes, infrastructure availability, healthcare provider support, peer influence, stigma/discrimination, and family support with HIV/AIDS preventive behavior among MSM at Talise Health Center, Palu. Methods: An explanatory mixed-methods design was used. The quantitative phase applied a cross-sectional approach with total sampling of 30 MSM, analyzed using univariate and bivariate (Chi-Square) tests. The qualitative phase involved case studies with in-depth interviews of 10 informants. Results: Overall, 43.3% of MSM showed good preventive behavior. Significant associations were found between infrastructure availability, peer influence, family support, and stigma/discrimination with HIV/AIDS preventive behavior (p<0.05). No significant relationship was observed for knowledge or healthcare provider support (p>0.05). Qualitative findings revealed that although MSM possessed adequate knowledge, this did not consistently lead to preventive actions. Conclusions: HIV/AIDS preventive behavior among MSM in Talise remains suboptimal. Key influencing factors include attitudes, family support, infrastructure, peer influence, and stigma/discrimination. Strengthening empowerment programs to reduce stigma and enhance community support is essential to improve prevention efforts.